Makna Lirik Lagu "Satu-satu" Karya IDGITAF dalam Kajian Semiotika Ferdinand de Saussure - Fahriza, Ade Ayu; Aulia Afniar Rahmawati (DIGICOM : Jurnal Komunikasi dan Media, 2024)
This research discusses the semiotic analysis of the meaning of motivation in the lyrics of the song "Satu-Satu" by Idgitaf. In this research, the author uses a semiotic method based on Saussure's ideas. Saussure's theory explains that signs have interconnected elements: signifier and signified. The results of the research of the song lyrics "Satu-Satu" by Idgitaf have meanings related to motivational messages. The motivation in question is the motivation to rise from the downturn of life and keep going because there will be a future for people who are strong to rise and survive. The songwriter also invites listeners to be patient and sincere with everything that has happened, because everyone must have bad experiences. The data analysis method is based on Ferdinand de Saussure's semiotics which focuses on the symbols themselves.